1993
DOI: 10.1288/00005537-199305000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Complications of laryngeal framework surgery (phonosurgery)

Abstract: The rising popularity of surgery involving the laryngeal framework (surgical medialization of immobile vocal folds, vocal fold tightening, pitch variation, etc.) has resulted in increasing case experience. Little has appeared in the literature regarding complications or long-term results of this type of surgery. Several years' experience in a major referral center with various types of laryngeal framework surgery has led to a small number of complications. These have included late extrusion of the prosthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 7 publications
5
79
2
3
Order By: Relevance
“…Two out of these 5 patients who had implant extrusion retained excellent glottic closure [5] . Tucker et al [9] have also reported this phenomenon in another series. However, no comment was made on the quality of voice of the patients, who retained excellent glottic closure following extrusion [9] .…”
Section: Discussionmentioning
confidence: 67%
“…Two out of these 5 patients who had implant extrusion retained excellent glottic closure [5] . Tucker et al [9] have also reported this phenomenon in another series. However, no comment was made on the quality of voice of the patients, who retained excellent glottic closure following extrusion [9] .…”
Section: Discussionmentioning
confidence: 67%
“…Es importante destacar que la terapia de voz debe continuar posterior a la cirugía, ya que esto ayudará a que el paciente adecúe sus nuevas condiciones anatomofisiológicas a la fonación (3) . Si bien es cierto que la tiroplastia tipo I es un procedimiento bastante seguro, no está exenta de posibles complicaciones; se ha descrito el eritema, edema y hematoma laríngeo (15)(16)(17) . Cotter, Avidano y col.…”
Section: Discusión Y Comentariosunclassified
“…Geç dönem komplikasyonlar ise; hematom oluflmas›, implant›n larenks lümenine ç›kmas›, kondrit, implant›n yer de¤ifltirmesi veya yerinden ç›kmas›d›r. 1,4,16,17 Bu çal›flmada medializasyon laringoplasti yap›lan 16 hastada herhangi bir komplikasyonla karfl›lafl›lmad›. Komplikasyonlar› engelleyebilmek ve operasyonun en iyi biçimde sonuçlanmas›n› sa¤layabilmek için cerrahi prosedürün süresinin uzun olmamas›, implant›n hastan›n yafl›na ve cinsine uygun olarak haz›rlanmas› ve do¤ru flekilde yerlefltirilmesi gerekir.…”
Section: Tart›flmaunclassified